FLOW THERMODYNAMICS. CHANGES IN THE KINETIC ENERGY OF THE CURRENT AND ITS MANIFESTATION IN NOZZLES AND DIFFUSERS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article describes the theoretical foundations of flow thermodynamics, energy exchange processes in gas and liquid flows, and their practical importance. The connections between the kinetic energy of the current, internal energy and pressure energy are analyzed, the working principle of nozzles and diffusers, as well as the laws of work in isochoric, isothermal, isobaric and adiabatic processes are explained. The first law of thermodynamics for gas flow and its physical content are revealed. The article shows the role of flow thermodynamics in understanding and improving the efficiency of energy circulation processes in gas turbines, compressors, heat exchangers and jet engines. The article analyzes the laws of thermodynamic change of flow kinetic energy, its role in gas and liquid movement processes, as well as energy exchange in nozzles and diffusers. It is justified that the kinetic energy of the current is important in creating useful work in heat machines and reactive devices.